Do Sports Programs Prevent Crime and Reduce Reoffending? A Systematic Review and Meta-Analysis on the Effectiveness of Sports Programs - Jugl, Irina (Journal of quantitative criminology, 2023)
Objectives Sports programs are widely implemented as measures of crime prevention. In contrast to their popularity, there is little systematic knowledge about their effectiveness. This systematic review and meta-analysis have been carried out to fill this gap. In a systematic review, we gathered data on evaluated prevention programs specifically designed to prevent crime and delinquency. We then conducted a meta-analytic integration with studies using at least roughly equivalent control groups for the program evaluation. Method To retrieve relevant literature, we conducted a comprehensive international literature search until June 2021 drawing on scientific databases. We also applied snow-balling searches and contacted practitioners in the field. Studies were eligible if they evaluated sports programs designed to prevent delinquency on primary, secondary, and/or tertiary level. We focused on crime-related outcomes and potentially underlying psycho-social factors. We made no restrictions regarding characteristics of the participants or other aspects such as duration of the program. Results 24 studies were eligible for our systematic review, from which only thirteen were included into our meta-analytic integration. We found a moderate effect of participation in sports programs on crime-related outcomes ( d = 0.36, p < .001). Participants showed a significant decrease in outcomes such as aggressiveness or anti-social behavior. We also analyzed psychological outcomes such as self-esteem or mental well-being, which also significantly improved when participating in sports programs ( d = 0.87, p < ..05). Conclusions Sports programs seem to be an effective measure of crime prevention. However, future research needs more sound evaluation designs and moderator analyses to better understand the functioning and improve the implementation of sports programs.